COGNITIVE IMPAIRMENTS AFTER STROKE - N. G. Katayeva; N. A. Kornetov; E. V. Karavayeva; V. A. Chistyakova; A. M. Eliseyeva (Неврология, нейропсихиатрия, психосоматика, 2010)
Thirty-two patients (mean age 53.912.4 years) with prior stroke were examined to clarify the pattern and degree of cognitive impairments depending on the site of a lesion. A control group comprised 32 subjects (mean age 52.112.9 years) without nervous system pathology. The authors made a complete clinical study to evaluate the neurological and mental status, a standardized interview, and A.R. Luria's neuropsychological tests. The patients with prior stroke were found to have lower values of auditory-verbal short-term and long-term memory, impaired concentration and voluntary attention scope. Mild cognitive disorders were established in middle-aged patients and moderate cognitive disorders of amnestic multifunctional type were in elderly patients. Auditory-verbal memory, visual gnosis, and some speech-related thought functions were impaired when in the involvement of the temporal and posterior frontal lobes in patients with prior stroke in the middle cerebral artery bed. Impaired visual image recognition and lower visual voluntary attention were detected in patients with prior stroke in the anterior and posterior cerebral arteries.